DEVELOPMENT OF DISTANCE LEARNING STRATEGIES BASED ON LEARNING MANAGEMENT SYSTEMS TO IMPROVE SELF-DIRECTED LEARNING AND STUDENTS’ UNDERSTANDING OF CONCEPTS - Ahkamsyadid Yusmaputra Salim; Deka Dyah Utami; Agus Wedi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Advances in information technology have significantly changed higher education, particularly through the implementation of distance learning. However, challenges remain, including low levels of student self-directed learning and inadequate conceptual understanding. This study aims to develop an LMS-based distance learning strategy in the form of digital learning modules that are valid, practical, and effective in improving student self-directed learning and conceptual understanding. This study uses a research and development (R&D) approach with Dick and Carey's instructional design model. Product validity was evaluated through expert validation, with results of 91% from subject matter experts, 80% from media experts, and 100% from learning design experts, indicating that the product is feasible for implementation. The usefulness and effectiveness were evaluated through small and large group trials and N-Gain analysis. The results of the independent learning questionnaire increased from 83% in the small group trial (practical category) to 97% in the large group trial (very practical category), indicating the high usefulness of the developed product. Additionally, N-Gain analysis showed a significant increase in students' conceptual understanding between pre- and post-tests. These findings indicate that LMS-based distance learning strategies effectively enhance students' self-directed learning and conceptual understanding.